EFEITO DA APLICAÇÃO DE INOCULANTES SOBRE O PERFILHAMENTO DO CAPIM-MARANDU. - MACHADO, Dayane Camargo,; TENÓRIO, Kamila de Paula,; RODRIGUES Nicolly Queiroz,; OLIVEIRA, Thayná Fernanda Silva,; ROCHETTI, Ana Carolina Alves, (ANAIS DO ENIC, 2023)
-